2001
DOI: 10.1046/j.1440-1746.2001.02474.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of alanine aminotransferase flare‐up among asymptomatic hepatitis C virus RNA carriers: A 10‐year follow‐up study

Abstract: Our results indicated that flare-up of ALT levels in asymptomatic HCV-RNA carriers with normal ALT levels occurs during the first 5 years of diagnosis, and that the presence of C100-3 and anti-HTLV-I antibodies are good predictors of a transient rise in ALT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…Approximately 20% of patients with normal ALT levels (N-ALT) show ALT elevation and fibrosis progression within 3-5 years [1][2][3][4][5], and consequently, 70-80% of N-ALT patients have mild to moderate fibrosis on liver biopsy. N-ALT patients have been excluded from conventional interferon (IFN) therapy, because their sustained virological response (SVR) rates on conventional IFN monotherapy have been reported to be only 6-15% [6][7][8][9], and ALT levels were noted to increase during or after treatment in 47-62% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 20% of patients with normal ALT levels (N-ALT) show ALT elevation and fibrosis progression within 3-5 years [1][2][3][4][5], and consequently, 70-80% of N-ALT patients have mild to moderate fibrosis on liver biopsy. N-ALT patients have been excluded from conventional interferon (IFN) therapy, because their sustained virological response (SVR) rates on conventional IFN monotherapy have been reported to be only 6-15% [6][7][8][9], and ALT levels were noted to increase during or after treatment in 47-62% of the patients.…”
Section: Introductionmentioning
confidence: 99%
“…It has been difficult to estimate precisely how many asymptomatic HCV-infected persons are at significant risk for progressive liver disease (17), because most of the epidemiological studies in Mexico on HCV infection have been conducted on blood donors, which has resulted in limited available information on the actual burden of HCV in the general population. In a previous study on blood donors (18), we found a 0.47% prevalence of HCV infection, which is the lowest prevalence reported in Mexico: intermediate prevalences were reported as 0.7-0.8% (19,20), with the highest prevalence being 1.47% (21).…”
Section: Discussionmentioning
confidence: 99%
“…59 However, patients with normal ALT, both monoinfected and coinfected, are at risk of developing significant liver disease and these patients should be evaluated and offered anti-HCV treatment if indicated. 38,[60][61][62][63][64][65] End-stage liver disease Cirrhosis. Cirrhosis occurs as a result of progressive destruction of hepatic parenchymal tissue that is gradually replaced by extracellular matrix protein.…”
Section: Alanine Aminotransferase Levelsmentioning
confidence: 99%